Pemberian makanan tambahan subtitusi tepung ikan gabus (PMT-tibus) dalam meningkatkan status gizi anak balita - Nadimin Nadimin (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2022)
Stunting is caused by inadequate nutrient intake in children and low parental knowledge, so it is necessary to provide additional food and nutrition education for parents. This study aims to determine the effect of providing supplementary food of snakehead fish flour substitution (called PMT-Tibus) on the nutritional status of children under five stunted. The study design used a randomized pretest-posttest control design. The study was conducted in Makassar City in 2019, using a sample of 24 people in each group. Group-1 was given PMT-Tibus with online nutrition education, while group-2 was only given online nutrition education. PMT-Tibus is given every day while the mother’s nutrition education is conducted periodically for one month. Nutritional status data was collected using anthropometric methods—processing and analyzing data using SPSS. WAZ of group-1 was increased by 0,11 ± 0,28. Otherwise, the WAZ of group-2 was decreased by -0,11 ± 0,42. HAZ of group-1 and group-2 increased (0,22 ± 0,31 vs 0,24 ± 0,31). WHZ of group-1 increased by 0,4 ± 0,04 and group-2 was decreased by -0,37 ± 0,68. There was a significant difference in WAZ and WHZ scores between the two groups, respectively, whit all p values < 0,05. Snakehead fish flour-based supplementary feeding (PMT-Tibus) and online nutrition education can improve the nutritional status of WAZ and WHZ in stunted toddlers.